A polydopamine-modified garnet–based polymer-in-ceramic hybrid solid electrolyte membrane for high-safety lithium metal batteries - Hailu Mengesha, Tadesu; Lemma Beshahwured, Shimelis; Wu, Yi–Shiuan; Wu, She–Huang; Jose, Rajan; Yang, Chunchen (Elsevier B.V., 2023)
Composite solid electrolyte (CSE) membranes combining the attractive properties of ceramic and polymer-based electrolytes have emerged as preferred electrolytes for all-solid-state lithium metal batteries (ASSLMBs). In this study, we used solution-casting to prepare a CSE membrane from a suspension of polydopamine (PDA)-modified Li6.28La3Zr2Al0.24O12 (LLZAO) filler (PDA@LLZAO), poly(vinylidene fluoride–co–hexafluoropropylene) (PVDF-HFP), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and succinonitrile (SN) as the middle layer and a matrix of PVDF-HFP, LiTFSI, and SN as both the top and bottom layers. The presence of PDA on the surface of LLZAO enabled the filler to percolate well within the polymer matrix. Consequently, a membrane based on PDA@LLZAO (CSE1) exhibited high ionic conductivity (4.01 × 10–4 S cm−1), a high lithium transference number (ca. 0.76), high tensile strength (29.09 MPa), and a stable electrochemical window (ca. 5.01 V vs Li/Li+) relative to those properties of a counterpart membrane (CSE0) having the same constituents as CSE1, but an unmodified LLZAO filler. The interfacial stability developed by the synergetic effect of the CSE1 membrane and Li metal anode enhanced the corresponding Li plating/stripping performance (2000 h) and critical current density (2.0 mA cm−2). Benefiting from this stable interfacial contact, an Al2O3@NCM811/CSE1/Li coin-type cell provided a discharge specific capacity of 136.46 mAh/g at a rate of 0.5C after 300 cycles, with a capacity retention of 86.22 % and a average coulombic efficiency of 99.16 % at 25 °C. Hence, our proposed strategy for preparing CSEs appears to be promising for use in ASSLMB applications.